2016
DOI: 10.1016/j.ejphar.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

The roles of miRNAs as potential biomarkers in lung diseases

Abstract: The roles of miRNAs as potential biomarkers in lung diseases, European Journal of Pharmacology, http://dx.doi.org/10. 1016/j.ejphar.2016.09.015 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable form. Please note that during the production process errors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
107
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 140 publications
(164 reference statements)
0
107
0
4
Order By: Relevance
“…New findings confirm the important role of specific miRNAs in biological processes such as proliferation, cell differentiation and evolution, modulation of immune responses in macrophages, and differentiation of heart and muscle cells . The role of miRNAs in the pathogenesis of various pulmonary diseases, including pulmonary fibrosis, obstructive pulmonary disease, lung cancer as well as asthma has been proven . Among the miRNAs involved in the progression of asthma, miRNA‐146a can be mentioned.…”
Section: Introductionmentioning
confidence: 77%
“…New findings confirm the important role of specific miRNAs in biological processes such as proliferation, cell differentiation and evolution, modulation of immune responses in macrophages, and differentiation of heart and muscle cells . The role of miRNAs in the pathogenesis of various pulmonary diseases, including pulmonary fibrosis, obstructive pulmonary disease, lung cancer as well as asthma has been proven . Among the miRNAs involved in the progression of asthma, miRNA‐146a can be mentioned.…”
Section: Introductionmentioning
confidence: 77%
“…In addition, studies showed that also other population characteristics such as age, weight, smoking status, and ethnicity can affect the identification of miRNA markers . Even other benign diseases such as chronic obstructive pulmonary disease (COPD), asthma, and tuberculosis can alter blood miRNA profiles and make some study participants unsuitable controls . Therefore, in this systematic review, we selected Western populations and excluded studies with disease controls to reduce the heterogeneity of included miRNAs caused by above‐mentioned factors.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that miRNAs are involved in a wide variety of biological processes, including cell proliferation, differentiation, metastasis, apoptosis and immune responses [16][17][18][19]; moreover, they also function as prognostic markers in the development and progression of ischemic renal diseases by targeting pertinent genes [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%